Diffusion tensor imaging in acute-to-subacute traumatic brain injury: a longitudinal analysis. Issue 1 (December 2016) - Edlow, Brian; Copen, William; Izzy, Saef; Bakhadirov, Khamid; van der Kouwe, Andre; Glenn, Mel; Greenberg, Steven; Greer, David; Wu, Ona
Abstract Background Diffusion tensor imaging (DTI) may have prognostic utility in patients with traumatic brain injury (TBI), but the optimal timing of DTI data acquisition is unknown because of dynamic changes in white matter water diffusion during the acute and subacute stages of TBI. We aimed to characterize the direction and magnitude of early longitudinal changes in white matter fractional anisotropy (FA) and to determine whether acute or subacute FA values correlate more reliably with functional outcomes after TBI. Methods From a prospective TBI outcomes database, 11 patients who underwent acute (≤7 days) and subacute (8 days to rehabilitation discharge) DTI were retrospectively analyzed. Longitudinal changes in FA were measured in 11 white matter regions susceptible to traumatic axonal injury. Correlations were assessed between acute FA, subacute FA and the disability rating scale (DRS) score, which was ascertained at discharge from inpatient rehabilitation. Results FA declined from the acute-to-subacute period in the genu of the corpus callosum (0.70 ± 0.02 vs. 0.55 ± 0.11, p < 0.05) and inferior longitudinal fasciculus (0.54+/−0.07 vs. 0.49+/−0.07, p < 0.01). Acute correlations between FA and DRS score were variable: higher FA in the body (R = −0.78, p = 0.02) and splenium (R = −0.83, p = 0.003) of the corpus callosum was associated with better outcomes (i.e. lower DRS scores), whereas higher FA in the genu of the corpus callosum (R = 0.83, p = 0.02) corresponded with worse outcomes (i.e. higher DRS scores). In contrast, in the subacute period higher FA in the splenium correlated with better outcomes (R = −0.63, p < 0.05) and no inverse correlations were observed. Conclusions White matter FA declined during the acute-to-subacute stages of TBI. Variability in acute FA correlations with outcome suggests that the optimal timing of DTI for TBI prognostication may be in the subacute period.